Disparidades salariales y la tasa interna de retorno a la educación privada en los docentes de la Universidad del Cauca. (2015)
This document aims to find the internal rate of return to private education from teachers of Universidad del Cauca (Popayan, Colombia) controlled by a set of social and economic variables. To achieve this, econometric models, exempt of endogeneity problems and sample selection biases, are built, as it includes academic productivity of teachers as an instrumental variable and additionally has population data. The results show, among many others, that the overall rate of return is lower for university professors compared with those found for all Colombia, and as it is a national and global pattern, this rate is lower for women than for men.